Genetic causes of short stature in children - Inglot, Jadwiga; Inglot, Julia; Szczepański, Michał; Bajak, Mateusz; Feret, Dominik Maciej; Mamczur, Maciej; Zapasek, Daniel; Słowik, Julia; Sowa, Damian; Kuliga, Marcin (Quality in Sport, 2024)
One of the essential elements of a visit to a pediatrician is a height measurement, which allows for the presentation of the child's growth tendency. Short stature is defined as a height that is lower than the average of a specific population, adjusted for age and sex, by at least 2 standard deviations, i.e., less than the 3rd percentile. Due to accompanying symptoms or their absence, the suspected etiology may vary. Genetic disorders are significant causes of short stature, especially among pediatric patients. The division distinguishes chromosomal, monogenic and polygenic disorders. Other possible causes of short stature may be the coexistence of chronic diseases or disorders of the endocrine system. In the case when the growth disorder is not a pathological condition, a variant of normal growth is diagnosed. In the diagnosis of short stature, in addition to a physical examination, it is sometimes necessary to perform laboratory or radiological tests, genetic tests, and specialist consultations.